PENATAAN PARKIR BERBASIS GREEN TRANSPORTATION DI POLITEKNIK NEGERI MEDAN - Putri, Wirdatun Nafiah; Kusumadi, Kusumadi; Oktaviani, Tetra; Mabrur, Muhamad; Hani, Sheila (UNIVERSITAS AL WASHLIYAH (UNIVA) MEDAN, 2025)
Arranging the parking area by planning the need for vertical parking spaces based on green transportation can be done to increase the UI Greenmentric score at Politeknik Negeri Medan, making the campus environmentally friendly. Therefore, the need for parking spaces is calculated. The planning of vertical parking spaces is based on parking population survey data conducted directly in the field as well as secondary data from previous research. From the calculations, the current need for motorcycle parking space at Politeknik Negeri Medan is 699 SRP, which will increase to 1,003.641 SRP in the next 10 years. Since only 800 SRP are available at the planned location, a multi-level motorcycle parking facility is being planned. Thus the existing parking area can be reduced by 4-7% with a score of 100 or 50% of the maximum value of indicator TR5. This figure increases from the calculation in the existing condition, which is 7-11% with a score of 50, representing 25% of the maximum value of the TR5 indicator. Keywords: Pedestrian, Parking Space, Green Transportation